2022
DOI: 10.1002/mrm.29173
|View full text |Cite
|
Sign up to set email alerts
|

An end‐to‐end AI‐based framework for automated discovery of rapid CEST/MT MRI acquisition protocols and molecular parameter quantification (AutoCEST)

Abstract: To develop an automated machine-learning-based method for the discovery of rapid and quantitative chemical exchange saturation transfer (CEST) MR fingerprinting acquisition and reconstruction protocols.Methods: An MR physics-governed AI system was trained to generate optimized acquisition schedules and the corresponding quantitative reconstruction neural network. The system (termed AutoCEST) is composed of a CEST saturation block, a spin dynamics module, and a deep reconstruction network, all differentiable an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 66 publications
0
43
0
Order By: Relevance
“…Recent studies by Cohen et al and Perlman et al have demonstrated the potential of deep learning for CEST imaging, but may not be accessible or transparent to a broader, non-technical audience [ 42 , 43 ]. However, we see the potential to incorporate AI-based methods into our system in the future to improve the performance and efficiency of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Cohen et al and Perlman et al have demonstrated the potential of deep learning for CEST imaging, but may not be accessible or transparent to a broader, non-technical audience [ 42 , 43 ]. However, we see the potential to incorporate AI-based methods into our system in the future to improve the performance and efficiency of the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several acceleration methods such as compressed sensing algorithms and deep learning approaches may be considered to overcome this issue. [57][58][59][60] Some limitations of this study should be noted. Although we aimed to observe the progression of renal injuries toward the chronic end using the cisplatin model, histological findings suggest insufficient fibrosis development compared to previous mouse CKD models.…”
Section: Discussionmentioning
confidence: 99%
“…Loktyushin et al proposed a supervised learning framework to discover MRI sequences for different tasks, including k-space trajectory and flip angle optimization, specific absorption rate (SAR) mitigation, and quantitative T mapping [ 204 ]. Perlman et al developed an end-to-end framework for generating rapid (less than 1 min) CEST acquisition protocols while simultaneously training a reconstruction network that extracts quantitative molecular maps from the raw data [ 205 ]. Kang et al developed a learning-based approach for the optimization of semisolid magnetization transfer MRF protocols [ 206 ] and demonstrated its applicability on human subjects.…”
Section: Artificial Intelligence (Ai) In Immunotherapy Treatment Moni...mentioning
confidence: 99%